Distributed Transaction Mode Considering Load Adjustment - Guodong HAN; Peirong JI; Fei WANG (Zhongguo dianli)
Considering the distributed market transaction mode, this paper proposes a two-layer optimization model that considers the coordination of optical storage and user load adjustment. Based on the transfer relationship between distribution network companies and optical storage investors, this paper proposes a market framework for distributed transactions. The market transaction model and solution algorithm are established, and the feasibility of the proposed method is verified based on the simulation example of the IEEE 33 bus distribution network system.